Nursery of red tilapia Oreochromis niloticus in a small-scale aquaponics system with different stocking densities - Hadiroseyani, Yani; May Sharly, Anita; Shafruddin, Dadang; Vinasyiam, Apriana (Jurnal Akuakultur Indonesia, 2023)
Aquaponics is a fish and hydroponic plant-rearing system that utilises fish waste as a plant nutrient. Because water quality can be maintained at an optimal level for fish in the system to enhance farming productivity. This study was conducted to evaluate the effects of fish density on the nursery stage of red tilapia in a small-scale aquaponic system. The study was conducted using a completely randomized design at three levels of stocking density, namely 250 fish/m2, 375 fish/m2, and 500 fish/m2 of red tilapia at an initial size of 6.8 ± 0.35 cm, with 30 net pots of bok choy plant as co-culture. The results that the increase in fish population escalated the productivity of both fish and vegetable in 30 days farming period. The stocking density did not affect fish survival 99 ± 0.82%, 97 ± 1.27%, and 97 ± 0.68%, respectively (p>0.05), but supported a better specific growth rate, namely 3.09 ± 0.30%/day; 3.57 ± 0.23%/day; 4.03 ± 0.04%/day (p